2011
DOI: 10.1039/c1an15542c
|View full text |Cite
|
Sign up to set email alerts
|

Resonance scattering spectral detection of trace ATP based on label-free aptamer reaction and nanogold catalysis

Abstract: Double-stranded DNA (dsDNA) cannot protect gold nanoparticles (AuNPs) in the presence of NaCl, and dsDNA interacted with adenosine triphosphate (ATP) to form stable G-quartet and a single-stranded DNA (DNA 2) that can protect AuNPs. The unprotected AuNPs were aggregated to AuNP aggregations (AuNPA) that exhibited a resonance scattering (RS) peak at 590 nm. The RS intensity at 590 nm decreased linearly when the ATP concentration increased in the range of 6.6-110 nM. The catalysis of AuNP-DNA 2 was stronger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Aptamers are single‐stranded oligonucleotide fragments that consist of 10 or more . With high specificity, high stability, simple synthesis and modification in vitro , aptamer can specifically bind the target substances and has been used for analysis and clinical testing . Resonance Rayleigh scattering (RRS) spectral method is simple, rapid and sensitive, and it has been applied to the analysis of nucleic acids, proteins and small molecules .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aptamers are single‐stranded oligonucleotide fragments that consist of 10 or more . With high specificity, high stability, simple synthesis and modification in vitro , aptamer can specifically bind the target substances and has been used for analysis and clinical testing . Resonance Rayleigh scattering (RRS) spectral method is simple, rapid and sensitive, and it has been applied to the analysis of nucleic acids, proteins and small molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Resonance Rayleigh scattering (RRS) spectral method is simple, rapid and sensitive, and it has been applied to the analysis of nucleic acids, proteins and small molecules . Nanogold, with good stability, good biocompatibility and RRS effect, has been applied in the aptamer–RRS analysis . Jiang et al .’s research group has reported an aptamer‐modified nanosilver RRS method for the detection of 0.02–1.06 µg/L melamine .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the cooled solution was filtered through 0.2 μm ultrafiltration membranes, and then stored in a brown glass bottles at 4°C for further use. Besides, the concentration of AuNPs, as a measure of the concentration of Au, was calculated as 7.3 × 10 −4 M [26].…”
Section: Preparation Of Aunpsmentioning
confidence: 99%
“…An aptamer is a short single‐stranded oligonucleotide containing 20–100 bases that can specifically recognize proteins, polypeptides, organic compounds, metal ions, various ligands, etc. It has been combined with RLS and a nano‐labeled technique to develop simple, sensitive and selective aptamer‐modified nanoparticle RLS methods for trace metal ions, melamine, ATP, adenosine and thrombin . To our knowledge, there is no report of an aptamer–RLS method for detecting the environmental estrogen bisphenol A (BPA).…”
Section: Introductionmentioning
confidence: 99%